2010
DOI: 10.1007/s10529-010-0242-8
|View full text |Cite
|
Sign up to set email alerts
|

PEGylation of alpha-momorcharin: synthesis and characterization of novel anti-tumor conjugates with therapeutic potential

Abstract: Alpha-momorcharin (alpha-MMC) is a ribosome-inactivating protein (RIP) with excellent cytotoxicity to tumor cells. However, its strong immunogenicity and short plasma half-life limit its clinical applications. To overcome this, we have to PEGylated alpha-MMC using a branched 20 kDa (mPEG) (2)-Lys-NHS. Homogeneous mono-, di- and tri-PEGylated alpha-MMCs were synthesized, purified and characterized. In vitro and in vivo analysis indicated that the serial PEG-conjugates preserved moderate anti-tumor activity with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 16 publications
2
38
0
Order By: Relevance
“…Four months later, the column worked for 30 times, and the result showed that the reusability of the gel is good. As was reported previously, with small scale, about 3.0 mg a-MMC was obtained from 2.5 g bitter melon after two ion exchange chromatographic steps on DEAE cellulose and mono-S FPLC [18], and 350 mg protein was purified from 200 g bitter melon seeds by the strategy of purification with four steps: supernatant extraction, ammonium sulfate fractionation precipitation, MacroCap SP chromatography and Superdex 75 chromatography [12]. Using immunoaffinity chromatography on the anti-a-MMC-McAb-Sepharose 4B, 196 mg a-MMC with 2.7% yield was obtained from 100 g bitter melon.…”
Section: Purification and Characterization Of A-momorcharin On Immunomentioning
confidence: 91%
See 2 more Smart Citations
“…Four months later, the column worked for 30 times, and the result showed that the reusability of the gel is good. As was reported previously, with small scale, about 3.0 mg a-MMC was obtained from 2.5 g bitter melon after two ion exchange chromatographic steps on DEAE cellulose and mono-S FPLC [18], and 350 mg protein was purified from 200 g bitter melon seeds by the strategy of purification with four steps: supernatant extraction, ammonium sulfate fractionation precipitation, MacroCap SP chromatography and Superdex 75 chromatography [12]. Using immunoaffinity chromatography on the anti-a-MMC-McAb-Sepharose 4B, 196 mg a-MMC with 2.7% yield was obtained from 100 g bitter melon.…”
Section: Purification and Characterization Of A-momorcharin On Immunomentioning
confidence: 91%
“…The slurry extract was stirred for overnight; after simple filtration through cheese cloth, the supernatant was fractionated by ammonium sulfate (35-70%). The deposits were dissolved in pH 7.0 50 mM Tris-HCl and dialyzed against the same buffer [12]. After centrifugation, the supernatant was applied to an anti-a-MMC McAb-Sepharose 4B column equilibrated with pH 7.0 50 mL Tris-HCl buffer; the column was sufficiently washed to remove unbound impurities with the pH 7.0 50 mM Tris-HCl buffer.…”
Section: Purification Of A-mmc By Anti-a-mmc Mcabsepharose 4bmentioning
confidence: 99%
See 1 more Smart Citation
“…The α-MMC was extracted from seeds of M. charantia according to the method of Bian et al (2010). JA, SA, ibuprofen, and ABT were purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Alpha-momorcharin (α-MMC), from a ribosome-inactivating protein (RIP) exhibited excellent cytotoxicity against tumor cells and strong immunogenicity and short half-life time in plasma. Bian et al [126] synthesized PEGylated-α-MMC using a branched mPEG. The results indicated that the complex preserved moderate anticancer activity and a longer circulation time with 36% acute toxicity and at most 66% immunogenicity decrease.…”
Section: The Pegylation Of Acpsmentioning
confidence: 99%